Direct Observation of the X-Ray Counterpart of the Hα Filaments and of the Sloshing Spiral in the Perseus Galaxy Cluster - Olivares-Sepulveda, V (IOP Publishing Ltd, 2025)
Deep Chandra observations of the Perseus galaxy cluster have allowed for the discovery of X-ray counterparts to the H alpha filamentary structures and of a sloshing spiral. However, both components are extremely faint, and their study is largely hindered by the volume-filling hot intracluster medium. Using the Poisson general morphological component analysis algorithm, a blind source separation method adapted for Poissonian statistics, we were able to extract detailed, clean morphological maps of these components. We then introduced a template fitting method to investigate their spectral characteristics. We report the first direct observation of similar to 1.35 keV low-energy emission from the sloshing spiral, and produce the most detailed and unpolluted map of the X-ray filaments thus far obtained.